Materials for biomedical engineering : organic micro and nanostructures - Holban, Alina Maria; Grumezescu, Alexandru Mihai (Elsevier, 2019)
Materials for Biomedical Engineering: Organic Micro- and Nanostructures provides an updated perspective on recent research regarding the use of organic particles in biomedical applications. The different types of organic micro- and nanostructures are discussed, as are innovative applications and new synthesis methods. As biomedical applications of organic micro- and nanostructures are very diverse and their impact on modern and future therapy, diagnosis and prophylaxis of diseases is huge, this book presents a timely resource on the topic. Users will find the latest information on cancer and gene therapy, diagnosis, drug delivery, green synthesis of nano- and microparticles, and much more.